SUT Stroke Specific Genogram: Application of Genogram on Screening for Individual at Risks of Stroke in Rural Thai Community - Singha-Dong, Naruemol; Bigelow, April (Global Journal of Medical and Clinical Case Reports, 2017)
Background: Non-communicable diseases including cardiovascular disease, hypertension, hyperlipidemia, and stroke are on the rise throughout the world. Further, there is a large proportion of individuals that have hyperlipidemia and hypertension that is not diagnosed, treated or controlled in low and middle income countries (LMICs). Notably, Asian countries including Thailand, have higher rates of mortality from stroke than from coronary heart disease. Despite several calls to action, there has been a lack of implementation of cardiovascular diseases prevention programs in LMICs largely due to insufficient investment in prevention efforts. One approach to combat these difficulties is to create a program or method aimed at early identification of those at risk for stroke. The purpose of this paper is to describe the use of a community stroke-risk focused genogram as a tool for identification of individuals in need of intervention and as a guide for the creation of educational prevention programs. Methods: The study was conducted in a rural village of Pakthongchai district, an area that has consistently had high prevalence of hypertension, rising prevalence of stroke, and access of care issues. The Stroke Specific Genogram (SSG) tool was adapted from a pictorial standard genogram with additional narratives to give a visual representation of each participant’s health history, record the history elicited, and identify actual problems and health risks based on elicited information. Stoke risk behaviors and current illness (es) were included in the SSG. Those behaviors included diet, hypertension prevention and control, stress management, smoking, and use of over the counter and prescription medications. Results: The total number of family members was 78, comprising of 37 males and 35 females. Level of education of most family members was four years and lower. Mr. S, the stroke index case, was shown in the second generation of the SSG. Causes of death of this family were hypertension, stroke, scleroderma, dengue hemorrhagic fever, typhoid fever, gun fire incident, and road accident, respectively. Of all 72 observed members, five members were known to have stroke with two deaths from stroke. One additional family member was recovering from stroke and immobile. From five generations, stroke risk factors were observed in all except one, the fifth generation. Conclusions and Recommendations: The SSG was able to identify stroke risk of the case family and suggests need for further investigation on a broader level. There were no risks identified in the fourth generation which we propose is due to the young age and minimal exposure at this time. Therefore, programs aimed at prevention are warranted. The SSG identified individuals at risk for stroke allowing nurses to focus attention on those most at risk and to implement proactive assessment, screening, and educational programs. The Stroke Specific Genogram can easily be incorporated into all aspects of community health nursing practice, from assessment for case finding to planning and implementing disease management strategies